Evaluasi Kebijakan Peraturan Majelis Dikdasmen Muhammadiyah tentang Kinerja Guru Di SMA Muhammadiyah 1 Gresik - Faizah, Any (Jurnal Kebijakan dan Pengembangan Pendidikan, 2014)
Any FaizahGuru Biologi SMA Muhammadiyah 1 Gresik.e-mail: anyfaizah69@yahoo.co.idAbstract:The approach used in this research is a qualitative approach using observation, questionnaires, interviews and documentation as the instruments of data collection. The results of this research showed that the regulation of Muhammadiyah Regional Leadership Council of Primary and Secondary Education about teachersâ€™ performance is proved effective in the implementation at State Senior High School of Muhammadiyah 1 Gresik. The implementation of regulation on teachersâ€™ performance assessment in State Senior High School of Muhammadiyah 1 Gresik addressed with full readiness, and dedicated in accordance with their each field. The effectiveness was shown from the values of performance achieved by teachers of State Senior High School of Muhammadiyah 1 Gresik, which obtain an average "good". This success cannot be separated from the hard work of the Muhammadiyah Regional Leadership Council of Primary and Secondary Education Gresik, and all the teachers and staff, as well as the strength of the rules and policies set by the education providers.Keywords: evaluation of policies, regulations council of basic education, the regional leadership of muhammadiyah.Abstrak:Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan menggunakan teknik observasi, kuesioner, wawancara dan dokumentasi sebagai alat pengumpulan data. Hasil penelitian menunjukkan bahwa peraturan Majelis Dikdasmen Pimpinan daerah Muhammadiyah tentang kinerja guru terbukti efektif dalam pelaksanaannya di SMA Muhammadiyah 1 Gresik. Pelaksanaan peraturan tentang penilaian kinerja guru di SMA Muhammadiyah 1 Gresik disikapi dengan penuh kesiapan, dan penuh dedikasi sesuai dengan bidangnya masing-masing. Efektivitas itu ditunjukkan nilai kinerja yang diraih oleh guru SMA Muhammadiyah 1 Gresik rata-rata â€œbaikâ€. Keberhasilan tersebut tidak terlepas dari kerja keras Majelis Dikdasmen Pimpinan Daerah Muhammadiyah Kabupaten Gresik, dan semua guru dan karyawan, serta kekuatan peraturan-peraturan dan kebijakan-kebijakan yang ditetapkan oleh penyelenggara pendidikan.Kata kunci: evaluasi kebijakan, peraturan majelis dikdasmen, pimpinan daerah muhammadiyah.